Mycobacterium Species Related to M. leprae and M. lepromatosis from Cows with Bovine Nodular Thelitis - Didier Pin; Véronique Guérin-Faublée; Virginie Garreau; Franck Breysse; Oana Dumitrescu; Jean-Pierre Flandrois; Gerard Lina (Emerging Infectious Diseases, 2014)
Bovine nodular thelitis is a granulomatous dermatitis associated with infection with acid-fast bacteria. To identify the mycobacterium responsible for this infection, we conducted phylogenetic investigations based on partial sequencing of 6 genes. These bacteria were identified as an undescribed Mycobacterium species that was phylogenetically related to M. leprae and M. lepromatosis.